Rainfall Attenuation on Earth-Satellite Microwave Link in a Tropical Environment - Odunewu, Paul Adekunle (Obafemi Awolowo University, 2014)
Rainfall is a major impairment to radiowave propagation at centimeters and millimetre wavebands, moreso in the tropics because of the intensity, frequency of occurrence and presence of large drops in tropical rainfall. In order to determine the vertical extent of rain (rain height) in the tropics, the characteristics of 0°C isotherm height have been studied using radiosonde data collected at three stations in Nigeria for three years at each station. One year rain rate data collected at Ile-Ife using an electronic rapid response rainguage have been analysed in order to obtain the cumulative rain rate distribution.